Kreativitas Guru Dalam Menggunakan Metode Pembelajaran Ski Di MA Proyek Universitas Al-Washliyah Medan - Abdul Ghani Jamora; Fadhilah Hilmy Nasution; Fenika Ardiyani; Nabila Ulkhaira (Prodi Perpustakaan dan Sains Informasi, 2021)
History of Islamic culture or SKI is a subject that studies and tells about events that occurred in the past regarding Islamic culture. Theoretically, teacher creativity is one of the factors that influence student learning activeness, because teacher creativity can create learning that is more active, dynamic, and does not saturate students so that students will be more enthusiastic and happy to receive learning. Besides that, the interaction between students can also affect the activeness of student learning. With good interactions between students at school that occur during teaching and learning activities inside the classroom and outside the classroom, it can foster learning motivation so that it can increase student learning activity. The aims of this study were to find out: (1) the effect of teacher creativity on student learning activity in class Xl in the subject of SKI at the MA UNIVA Medan Project, (2) to find out the effect of interaction between students on the learning activity of class Xl students in the subject matter of SKI MA UNIVA Medan Project, (3) determine the effect of teacher creativity and interaction between students on the learning activity of class X students in SKI subjects in SKI MA Project UNIVA Medan.